Long noncoding RNA MALAT1 in exosomes drives regenerative function and modulates inflammation-linked networks following traumatic brain injury - Niketa A. Patel; Lauren Daly Moss; Jea-Young Lee; Naoki Tajiri; Sandra Acosta; Charles Hudson; Sajan Parag; Denise R. Cooper; Cesario V. Borlongan; Paula C. Bickford (Journal of Neuroinflammation, 2018)
Abstract Background Neuroinflammation is a common therapeutic target for traumatic brain injury (TBI) due to its contribution to delayed secondary cell death and has the potential to occur for years after the initial insult. Exosomes from adipose-derived stem cells (hASCs) containing the long noncoding RNA MALAT1 are a novel, cell-free regenerative approach to long-term recovery after traumatic brain injury (TBI) that have the potential to modulate inflammation at the genomic level. The long noncoding RNA MALAT1 has been shown to be an important component of the secretome of hASCs. Methods We isolated exosomes from hASC containing or depleted of MALAT1. The hASC-derived exosomes were then administered intravenously to rats following a mild controlled cortical impact (CCI). We followed the rats with behavior, in vivo imaging, histology, and RNA sequencing (RNA Seq). Results Using in vivo imaging, we show that exosomes migrate into the spleen within 1 h following administration and enter the brain several hours later following TBI. Significant recovery of function on motor behavior as well as a reduction in cortical brain injury was observed after TBI in rats treated with exosomes. Treatment with either exosomes depleted of MALAT1 or conditioned media depleted of exosomes showed limited regenerative effects, demonstrating the importance of MALAT1 in exosome-mediated recovery. Analysis of the brain and spleen transcriptome using RNA Seq showed MALAT1-dependent modulation of inflammation-related pathways, cell cycle, cell death, and regenerative molecular pathways. Importantly, our data demonstrates that MALAT1 regulates expression of other noncoding RNAs including snoRNAs. Conclusion We demonstrate that MALAT1 in hASC-derived exosomes modulates multiple therapeutic targets, including inflammation, and has tremendous therapeutic potential for treatment of TBI.